Epidemiologi Kriptosporidiosis - Esy Maryanti (Jurnal Ilmu Kedokteran, 2011)
Cryptosporidiosis is a disease caused by Cryptosporidium sp. Cryptosporidium sp. are single cell of coccidian caninfected human and animals. Cryptosporidiosis are considered a cause of emerging and opportunistic infections inhuman. Oocysts of Cryptosporidium are ovoid or spherical and 4 to 6 micrometers diameters. The parasite is located inthe brush border of the epithelial cells of the small intestine. Currently, eight species of Cryptosporidium are known toinfect human and there are two species, C parvum and C muris which most common species reported to infect childrenand immunocompromised patient especially AIDS patient with diarrhea.